Embedded remote group environment through modification in MACBETH – an application of contractor’s selection in construction - Khoso, Ali Raza; Yusof, Aminah Md.; Chen, Zhen-Song; Wang, Xian-Jia; Skibniewski, Mirosław J.; Memon, Nafees Ahmed (Journal of Civil Engineering and Management, 2021)
A group decision environment has profound roots in MACBETH (Measuring Attractiveness by a Categorical Based Evaluation Technique) analysis which indeed has plentiful advantages; however, many researchers envisage the embedded group decision system as an impediment in actual implementation. The accessibility of explicit interaction of decision makers at a single platform in the form of embedded group decision environment is a great impediment to the researchers. Accordingly, this research aims to tailor a novel alternative system of dealing with the embedded group decision under a remote group decision environment via integrating MACBETH and Exploratory Factor Analysis. The study finds that an embedded remote group decision making system could serve as an alternative system of group decision making which has plentiful perks in group decision applications. This system could help researchers to carry out research without confusing in embedded group decision environment but including all decision-makers in the model. The implication of proposed system is not only limited to MACBETH; however, due to system’s versatility, a similar approach could be fruitful for other group-related environments involving collective decisions.Please view correction statement: Corrigendum: Embedded remote group environment through modification in MACBETH - an application of contractor’s selection in construction